Usefulness of Cytokine Gene Polymorphisms for the Therapeutic Choice in Japanese Patients with Rheumatoid Arthritis - Tsujimoto, Saki (Int J Gen Med, 2021)
BACKGROUND: Rheumatoid arthritis (RA) is characterized by systemic synovitis with bone erosion and joint cartilage degradation. Although the analysis of polymorphisms in cytokine-encoding genes is important or understanding the pathophysiology of RA and selecting appropriate treatment for it, few studies have examined such single-nucleotide polymorphisms (SNPs) specifically in Japanese patients. This study was established to investigate the associations between polymorphisms in cytokine-encoding genes, autoantibodies and therapeutic responses in Japanese RA patients. METHODS: The subjects in this study consisted of 100 RA patients and 50 healthy controls. We extracted data on sex, age, disease duration, rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP) antibody, and therapeutic responses, including to methotrexate (MTX) and biological disease-modifying antirheumatic drugs (DMARDs). Genomic DNA was isolated from peripheral blood, which was genotyped for IL-10, TNF-α, TGF-β(1), and IFN-γ polymorphisms. RESULTS: Regarding IL-10 (−592 C/A and −819 C/T), significant decreases in the frequencies of the IL-10 (−592) CC genotype and (−819) CC genotype were found in RA patients compared with the levels in controls. For IFN-γ (+874 T/A), a significant decrease in the frequency of the TT genotype was found in RA patients compared with that in controls. Regarding TGF-β(1) (+869 T/C), patients with positivity for anti-CCP antibody had a significantly lower frequency of the CC genotype than those with negativity for it. Furthermore, the IL-10 (−592) CC genotype and (−819) CC genotype might be related to the biological DMARD-response. CONCLUSION: Our results suggest that the analysis of polymorphisms in cytokine-encoding genes may be useful when selecting treatment for Japanese RA patients.